Impact Of Exposure To Phymar Csl Application On The Activity Of Pollinating Bee Tetragonula Laeviceps Smith (Hymenoptera; Apidae) - Siti Anisa; Awaluddin Awaluddin; Rahayu Rahayu; Waode Siti Anima Hisein (Fakultas Teknologi Pertanian Unsultra, 2026)
The stingless bee Tetragonula laeviceps (Hymenoptera; Apidae) is an important pollinator that supports agricultural productivity, yet its population may be affected by pesticide use, including botanical pesticides. This study aimed to evaluate the toxicity of the botanical pesticide Phymar CSL to T. laeviceps, assess the effects of its residues on bee survival, and determine whether Phymar CSL acts as an attractant or repellent. The study was conducted at the Plant Protection Laboratory, Faculty of Agriculture, Halu Oleo University, from November-December 2025. Toxicity tests were carried out using five concentrations of Phymar CSL (5, 10, 20, 40, and 80 mL/L) mixed with a 10% honey solution and analyzed using probit analysis, while residue and preference tests were analyzed descriptively. The results showed that the LC₅₀ value of Phymar CSL for T. laeviceps was 16.194 mL/L, which was lower than the recommended field application dose (20 mL/L). Residue exposure resulted in relatively low bee mortality, even at LC₅₀ and LC₉₅ concentrations. Preference tests using a Y-tube olfactometer indicated that Phymar CSL was not attractive but exhibited repellent properties toward T. laeviceps. These findings suggest that although direct exposure to Phymar CSL may pose toxic risks to T. laeviceps, its residues are relatively safe and do not attract bees; therefore, application should be avoided during flowering stages and peak foraging periods to support pollinator conservation and sustainable agriculture.